Web-Based Financial Information System Testing of PT Perta Sakti Abadi Using the Black Box Testing Method - Meliala, Rajhaga Jevannya; Anggraeni, Aulia; Holik, Wildan; Manik, Jonser Steven Rajali; Hakim, Ghaeril Juniawan Parel; Mindara, Gema Parasti; Wicaksono, Aditya (Asosiasi Riset Teknik Elektro dan Infomatika Indonesia, 2025)
Software testing is a critical phase in information system development to ensure the system's quality and reliability. This study aims to evaluate the reliability and functionality of PT Perta Sakti Abadi's financial information system using the black-box testing method with the Equivalence Partitioning (EP) technique. This technique allows input data to be grouped into valid and invalid categories, minimizing test cases without reducing testing coverage. The testing focuses on the login feature as the system's primary component by evaluating various input combinations. The testing scenarios include boundary conditions to ensure the system handles inputs correctly in various situations.The results indicate that the system successfully verifies valid credentials, rejects access with invalid data, and provides informative error messages. Additionally, the system demonstrates resilience in handling testing scenarios, including inputs with special characters and empty fields. Input validation mechanisms function optimally, supporting secure user access and ensuring the login feature aligns with functional specifications. This successful testing forms a strong foundation for testing other modules, such as multi-level authentication and data encryption. Thus, the Equivalence Partitioning technique within the black-box testing method proves effective in enhancing the quality of web-based financial information systems.